Analysis of Travel Mode Choice To Hospitals concerning Socio-Economic Attributes (Case Study: Shiraz Downtown) - sanam afaridi; fereshte ahmadi; ali soltani; mahmood mohamdi (تحقیقات کاربردی علوم جغرافیایی)
Optimal condition of accessibility and rapid, easy, and safe travel to health_ treatment land uses can be performed by the systematic analysis of transportation sub-systems like behavior. Developed countries are in essential need of proper transportation system for better accessibility. This paper aims to develop model, considering mode chains as well as the individual characters. This study benefits the analytic and quantitative research methods in developing mode choice model to evaluate the movement pattern of travel to health care centers in Shiraz central district (district 1). Each mode is the dependent variable whereas the socioeconomic characters are the independent variables. Filled questionnaire and geographical information system is used in collecting data. To generate the model, multinomial logit model was used that shows public transport like metro and bus are not the popular modes in access to hospitals. Movement pattern cognition in accessibility to special urban land uses, has an efficient role in urban policies and planning, which can be generalized and indigenize to healthcare travel behavior in other geographical areas. Results show that car ownership will increased the private car travel rate 8 times according to beta coefficient.. Taxi is the mode which is used in all three travels. People with lowest range of income and education use bus as their mode. Besides metro travel also has significant relation with low level of income and increase the travel rate 9 times. Keywords: logit Model, Hospital, vehicle, travel mode, Shiraz City.